"Cascaded Rocket" Nanosystems with Spatiotemporal Separation for Triple‐Synergistic Therapy of Alzheimer's Disease. Issue 11 (24th February 2022) - Liu, Ruiyuan; Yang, Jun; Qiu, Xinyu; Ji, Weihong; Shen, Jie; Li, Yan; Lu, Zhiguo; Wu, Yanyue; Wang, Wenli; Wang, Jing; Hao, Jifu; Zhang, Xin
Abstract: Alzheimer's disease (AD) remains an incurable disease due to the intricate pathogenesis. The neuropathological hallmarks include extracellular amyloid‐ β (A β ) plaques, tau phosphorylation and extensive oxidative stress in neurons, which facilitate the progression of AD. Based on the complex etiology, a spatiotemporally "cascaded rocket" delivery system (DPH/TPGAS NPs) with metal ion/enzyme responses is established in this study for triple‐synergistic AD treatment. After targeting and permeating the blood‐brain barrier (BBB), the histidine units in the DPH chelate excess metal ions at the extracellular microenvironment, restraining the formation of A β aggregates, inducing the first‐stage separation. Then, the remanent system targets neuronal cells and triggers the second separation with cathepsin B for reducing the level of phosphorylated tau and oxidative stress. Accordingly, the DPH/TPGAS NPs can achieve spatiotemporal drug release, which results in enhanced synergistic therapeutic effects both in the extracellular and intracellular region of the AD brain. After treating with DPH/TPGAS NPs, the memory deficits, levels of Aβ and phosphorylated tau, inflammation and neuron damages are remarkably ameliorated in 3 × Tg‐AD mice. Therefore, this "cascaded rocket" delivery system has great potential to serve as a powerful platform and provides a new horizon to the therapeutic strategy for AD and other brain diseases' treatments. Abstract : Based on the complex etiology of Alzheimer's disease (AD), a spatiotemporally "cascaded rocket" delivery system (DPH/TPGAS NPs) with two‐stage separation is established. The NPs can achieve spatiotemporal drug release, which synergistically restrain the extracellular A β toxicity, reduce the intracellular tau phosphorylation and suppress the oxidative stress. The NPs provide a promising strategy for the treatment of AD and other brain diseases.